The Effect of Email on Students’ Writing Skills at the Eighth Graders of MTs. Mu’allimat NW Kelayu in the School Year 2017-2018 - Jumatriadi Jumatriadi (FONDATIA, 2018)
Writing is one of language skill that must be mastered by the language learners.The teacher must be selective in relevant methode, media and technique, that is can engage the students to be more effective and creative in achieve the goal of learning. One of the media that is used in language teaching is email,because, it may motivate and reinforce any language skill the students. And as graphic commuicatioan to give the certain massage accurately and short with use the language it easy to be understand.The statement of the problemsof thisresearch are; (1) Is there any effect of email on students‟ writing skillsat the eighth graders ofMTs. Mu’allimat NW Kelayu in the school year2017-2018? (2) To what extent is the effect ofemail on students‟ writing skills at the eighth graders of MTs. Mu’allimat NW Kelayu in the school year2017-2018?. This study belongs to a pre experimental research. The population was the eighth grade students of MTs. Mu’allimat NW Kelayu consisting of two classes. However the present researcher just took one class as sample there were 20 students as the experimental class. To get the data, the present researcher used research instrument namely written test.The result of data analyze, the present researcher found out the result rtest was 0.52 and r tablewas 0.38 with df = 5% from the total of sample was twenty students. It means rtest was higher than rtable (0.52> 0.38). So that, the present researcher concluded alternative hypothesis (Ha) was accepted, and null hypothesis (Ho) was rejected. It means that there was effect of email on students‟ writing skillsatthe eighth graders of MTs. Mu’allimat NW Kelayu in the school year2017-2018